Supervisi Akademik dalam Meningkatkan Hasil Penilaian Kinerja Guru Berbasis E- Kinerja di SDN Warungdowo I Pohjentrek Pasuruan - Khotimah, Husnul; Wahidmurni, Wahidmurni; Indah Aminatuz Zuhriyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to reveal the process of implementing academic supervision and its contribution in improving the results of teacher performance assessment based on E-Performance at SDN Warungdowo I Pohjentrek Pasuruan. The research method used is descriptive qualitative, with data collection techniques in the form of observation, document study, and visual analysis. The results of the study indicate that academic supervision is carried out through three stages, namely pre-supervision, direct supervision, and post-supervision, with the division of small groups led by senior teachers. This supervision not only helps improve the quality of learning in the classroom, but also becomes the basis for assessing teacher performance in the E-Performance application. The conclusion of this study is that the implementation of structured and collaborative academic supervision significantly supports improving the quality of teacher performance, although there are still several obstacles such as time constraints and instruments that have not been varied. Keywords: E-Performance, Principal, Teacher Performance Assessment, Academic Supervision